أثر التدريس باستخدام نموذج الجيل الجديد المدمج لتعليم العلوم (NexGenReady-Science) في اكتساب طلاب الصف السادس الأساسي للمفاهيم العلمية والاحتفاظ بها - الرواشدة، أحمد أعبد محمود; القادري، سليمان أحمد (الجامعة الأردنية - عمادة البحث العلمي, 2019)
This study aimed to investigate the effect of teaching 6th grade students science using new online science education model called Next Generation Science model ((NexGenReady-Science) on students acquisition and retention of scientific concepts. To achieve the study purposes, a test consisted of (25) items was developed. The validity and reliability of the test were verified. It was applied to two classes (41 students), supervised by Directorate of education of Southern Mazar, for the academic year 2015- 2016, were chosen intentionally to participate in the study. They were assigned randomly to the experimental group, consisting of (20) students (studied by the new online Next Generation Science Education Model ((NexGenReady-Science)) and control groups, consisting of (21) students (studied by the traditional teaching method). The application period was 2 months ended by collecting and analyzing the data. Results of the study showed that: There were statistically significant differences at(α = 0.05) between the two groups on two dimensions of the test (concrete and abstract concepts) and the overall average and the deferred test of students in favor of the experimental group. The study recommended the adoption of Next Generation Science Education Model ((NexGenReady-Science) in teaching science. It also recommended further studies on the aforementioned model to see its impact on other variables and other classroom levels.
هدفت هذه الدراسة إلى تقصي أثر التدريس باستخدام نموذج برنامج الجيل الجديد المدمج لتعليم العلوم (NexGenReady-Science) في اكتساب طلاب الصف السادس الأساسي للمفاهيم العلمية والاحتفاظ بها .ولتحقيق ذلك تم تطوير اختبار لاكتساب المفاهيم العلمية والتحقق من صدقه وثباته، وتم تطبيقه على عينة قصدية بلغ عدد أفرادها (41) طالباً من الصف السادس الأساسي التابعة لمديرية تربية المزار الجنوبي للعام الدراسي 2015- 2016م. وتم تعيينهم بالطريقة العشوائية إلى مجموعتين :تجريبية، وعددهم (20) طالباً (درست بواسطة نموذج الجيل الجديد المدمج لتعليم العلوم (NexGenReady- Science))، وضابطة، وعددهم (21) طالباً) درست بالطريقة الاعتيادية)، وتم جمع البيانات وتحليلها بعد انتهاء التجربة التي استمرت شهرين تقريبا. أظهرت نتائج الدراسة وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (α= 0.05) بين المجموعتين في اكتساب المفاهيم العلمية بنوعيها :(المحسوس والمجرد) وفي الاحتفاظ بهما، ولصالح أفراد المجموعة التجريبية. وقد أوصت الدراسة بتبني نموذج الجيل الجديد المدمج لتعليم العلوم (NexGenReady-Science)في تدريس العلوم، وبإجراء مزيد من الدراسات حول فعالية النموذج المذكور في متغيرات بحثية جديدة، وعلى صفوف دراسية أخرى.
Keywords: تدريس العلوم -- نموذج الجيل الجديد المدمج لتعليم العلوم -- المفاهيم العلمية -- الصف السادس الأساسي